The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5455/rmj.2007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the level of perceived organisational transparency among healthcare providers working for the Ministry of Health, Saudi Arabia

Abstract: Objective: To identify the level of perceived organisational transparency among healthcare providers working for the Ministry of Health. Methodology: Four hundred and twenty participants in three ministry of health facilities were surveyed using a descriptive cross-sectional correlational design and validated survey data. Results: The total average of all responses on all items of the organisational transparency was 3.37± 0.66. Organisational transparency was perceived by nurses more than physicians and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…This implies that the level of transparency within the organization is highly prominent. This finding contradicted the results presented by Almuqati et al, (2022) who reported in their research that healthcare providers perceived organizational transparency to be of moderate level. Additionally, Al-Subaie, (2010) discovered that the commitment to transparency within the Saudi government sector was low.…”
Section: Organizational Corruption and Its Relation To Organizationalcontrasting
confidence: 97%
See 2 more Smart Citations
“…This implies that the level of transparency within the organization is highly prominent. This finding contradicted the results presented by Almuqati et al, (2022) who reported in their research that healthcare providers perceived organizational transparency to be of moderate level. Additionally, Al-Subaie, (2010) discovered that the commitment to transparency within the Saudi government sector was low.…”
Section: Organizational Corruption and Its Relation To Organizationalcontrasting
confidence: 97%
“…These results highlight the prominence of the information system in fostering transparency within the organization while indicating the need for improvement in promoting accountability among nurses. In a similar vein, Al-Nashmi, (2015) and Almuqati et al, (2022) elucidated that participants held a higher perception of the ministry's endeavors in furnishing comprehensive information, surpassing their perception of other dimensions of transparency.…”
Section: Organizational Corruption and Its Relation To Organizationalmentioning
confidence: 92%
See 1 more Smart Citation